Identifying legal problems in real property timeshare agreements for consumers in Malaysia / Aldric Tinker, Azira Aziz - Tinker, Aldric; Aziz, Azira (2008)
Timeshare schemes in the forms of resorts, hotels and other recreation-based properties have grown in popularity since its inception particularly in Malaysia. However, there is still a severe lack in regulatory measures concerning timeshare companies, timeshare agents and the rights of consumers. The existence of rogue agents in the field resulted in problems faced by timeshare owners and consumers. By conducting this research, we aimed to uncover its inadequacies and proffer solutions that would resolve this conflict between balancing the rights of the consumers and the companies who offer timeshare. We have collected information from various related journals, periodicals, articles and cases. In addition to that, we had also conducted interviews with timeshare lawyers regarding their opinions on this problem and their expertise in the area. We also interviewed a representative from the National Consumer Crimes Centre to assist our research. Our research emphasizes on finding a solution for the rapid development and yet the lack of regulation on the timeshare industry in Malaysia, balancing it with the right of consumers. We have concluded that it is insufficient, and have added suggestions and recommendations. Its implementation however, would be a long and winding road.